Patterns of regional recurrence according to molecular subtype in patients with pN2 breast cancer treated with limited field regional irradiation. (27th October 2022) - Cho, Won Kyung; Park, Won; Jeong, Yuri; Kim, Haeyoung; Kim, Nalee
Abstract: Objective: There is little evidence regarding the radiotherapy modification based on molecular subtypes in breast cancer. This study aimed to identify the risk and patterns of regional recurrence according to molecular subtype in patients with pN2 breast cancer. Methods: We identified 454 patients who underwent radical surgery for breast cancer with 4–9 axillary lymph node metastases. All patients underwent axillary lymph node dissection, adjuvant chemotherapy and limited-field regional nodal irradiation. The rates and patterns of regional recurrence were compared between the following three subgroups: luminal type (estrogen receptor- and/or progesterone receptor-positive), HER2-type (estrogen receptor- and progesterone receptor-negative and HER2-positive) and triple-negative type (estrogen receptor-, progesterone receptor- and HER2-negative). Results: Regional recurrence occurred in 18/454 patients (4%). The risk of regional recurrence was higher in the triple-negative (hazard ratio 7.641) and HER2-type (hazard ratio 4.032) subtypes than in the luminal subtype. The predominant pattern of regional recurrence was inside the radiotherapy field in triple-negative breast cancer and outside the radiotherapy field in HER2-type and luminal-type cancers. Conclusions: In patients with pN2 breast cancer, the risk of regional recurrence was higher in the triple-negative and HER2-type than in the luminal type. In-field recurrence was predominant in triple-negative cancer, while out-field recurrence was frequent in luminal and HER2-type breast cancers. Abstract : We explored the patterns of regional recurrence according to subtypes in pN2 breast cancer. In-field recurrence was predominant in triple-negative type, while out-field recurrence was frequent in HER2-type and luminal type.